Beyond The Intention of Generation Z to Work at Islamic Banks: Case of Universitas Islam Negeri Antasari and Universitas Lambung Mangkurat Students - Mujalipah , Mujalipah; Hidayat, Muhammad Rifqi (At-Taradhi Jurnal Studi Ekonomi, 2024)
This study examines the influence of learning motivation, perception of Islamic banks, and religiosity on students' interest in careers in Islamic banks. The research was conducted at Antasari State Islamic University and Lambung Mangkurat University with 100 respondents selected using purposive sampling. Data were collected through a Likert scale questionnaire and analyzed using SPSS with multiple linear regression. The results of the study showed that religiosity had a significant influence on career interest in Islamic banks, while learning motivation and perception of Islamic banks partially did not show a significant influence. However, simultaneously, these three variables have a significant influence on career interest with a contribution of 69.1%. These findings show that religiosity is a decisive factor in shaping students' career preferences, as well as indicating the need for Islamic banks to adjust branding strategies and work policies to attract the interest of Generation Z.           Penelitian ini mengkaji pengaruh motivasi belajar, persepsi terhadap bank syariah, dan religiusitas terhadap minat mahasiswa dalam berkarir di bank syariah. Penelitian dilakukan di Universitas Islam Negeri Antasari dan Universitas Lambung Mangkurat dengan melibatkan 100 responden yang dipilih menggunakan metode purposive sampling. Data dikumpulkan melalui kuesioner skala Likert dan dianalisis menggunakan SPSS dengan regresi linier berganda. Hasil penelitian menunjukkan bahwa religiusitas memiliki pengaruh signifikan terhadap minat berkarir di bank syariah, sedangkan motivasi belajar dan persepsi terhadap bank syariah secara parsial tidak menunjukkan pengaruh yang signifikan. Namun, secara simultan, ketiga variabel ini memiliki pengaruh signifikan terhadap minat berkarir dengan kontribusi sebesar 69,1%. Temuan ini menunjukkan bahwa religiusitas merupakan faktor penentu dalam membentuk preferensi karir mahasiswa, serta mengindikasikan perlunya bank syariah menyesuaikan strategi branding dan kebijakan kerja untuk menarik minat generasi Z.